Ultrasound-Mediated Microbubble Destruction Inhibits Skin Melanoma Growth by Affecting YAP1 Translation Using Ribosome Imprinting Sequencing - Wei, Tianhong; Li, Lan; He, Zhiyou (Frontiers in Oncology, 2021)
Cutaneous melanoma (CMM) is a skin tumor with a high degree of malignancy. BRAF resistance imposes great difficulty to the treatment of CMM, and partially contributes to the poor prognosis of CMM. YAP is involved in the growth and drug resistance of a variety of tumors, and mechanical signals may affect the activation of YAP1. As a novel ultrasound treatment technology, ultrasound-mediated microbubble destruction (UMMD) has been reported to have a killing effect on isolated CMM cells. In this study, the tumor tissue samples were collected from 64 CMM patients. We found that YAP1 mRNA expression was irrelevant to the clinicopathological characteristics and prognostic survival of the CMM patients. The drug-resistant cell line was constructed and subcutaneously implanted into nude mice, which were further separately treated with UMMD, ultrasound (US), and microbubbles (MB). The result showed that UMMD significantly inhibited the growth of tumor tissues. Ribosome imprinting sequencing (Ribo-seq) is a genetic technology for studying protein translation at genetic level. Ribo-seq, RNA-seq, and RT-qPCR were applied to detect YAP1 expression in CMM mouse tumor tissues. Ribo-seq data revealed that UMMD greatly up-regulated the expression of YAP1, interestingly, the up-regulated YAP1 was found to be negatively correlated with the weight of tumor tissues, while no significant change in YAP1 expression was detected by RNA-seq or RT-qPCR assay. These results indicated that UMMD could inhibit the tumor growth of drug-resistant CMM by affecting the translation efficiency of YAP1, providing a strong basis for the clinical treatment of UMMD in CMM.